2014
DOI: 10.1002/ange.201402939
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Induced Electron Transport from Small to Large Nanoparticles in Bimodal Gold Nanoparticle‐Loaded Titanium(IV) Oxide

Abstract: A key to realizing the sustainable society is to develop highly active photocatalysts for selective organic synthesis effectively using sunlight as the energy source. Recently, metal-oxide-supported gold nanoparticles (NPs) have emerged as a new type of visible-light photocatalysts driven by the excitation of localized surface plasmon resonance of Au NPs. Here we show that visible-light irradiation (l > 430 nm) of TiO 2 -supported Au NPs with a bimodal size distribution (BM-Au/TiO 2 ) gives rise to the long-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…The 3DOM nanostructure with a large surface area and porosity makes the reactant diffusion facile into the bulk of catalyst and hence provide fast intraparticle molecular transfer. Secondly, the introduction of Au nanoparticles in composites can effectively extend the spectral response from UV to visible area owing to Au SPR [34,35]. At last, the electrons assembled on the CB of TiO 2 and positive charges (h + ) gathered on Au nanoparticles.…”
Section: Photocatalytic Mechanismmentioning
confidence: 99%
“…The 3DOM nanostructure with a large surface area and porosity makes the reactant diffusion facile into the bulk of catalyst and hence provide fast intraparticle molecular transfer. Secondly, the introduction of Au nanoparticles in composites can effectively extend the spectral response from UV to visible area owing to Au SPR [34,35]. At last, the electrons assembled on the CB of TiO 2 and positive charges (h + ) gathered on Au nanoparticles.…”
Section: Photocatalytic Mechanismmentioning
confidence: 99%
“…However, in addition to the low efficiency and poor selectivity, the use of the unstable and toxic CdS photocatalyst makes this process unfavourable for industrial applications (Table 1 , entry 1). Azobenzene can be successfully synthesised at room temperature (RT) by using a Au supported TiO 2 photocatalyst (Table 1 , entry 2) 19 . A recent study has demonstrated that selective photosynthesis of azobenzene can also be realised at elevated temperature (90 °C), by using a cheaper metal (Cu) supported on graphene (Table 1 , entry 3) 17 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“… a High-pressure Hg lamp (0.007 W cm −2 ) 18 b 0.01 M KOH, 300 W Xe lamp (>430 nm, 0.01 W cm −2 ) 19 c 0.01 M KOH, 300 W Xe lamp (400–800 nm, 0.15 W cm −2 ) 16 d N3 dye on TiO 2 with Pt, triethanolamine (TEOA) as scavenger, 3 W 530 nm LED 26 e 500 W Xe lamp (450–600 nm, 0.083 W cm −2 ) 24 f LED lamp (>420 nm, 30 × 3 W), Na 2 S and Na 2 SO 3 in water 23 g 0.01 M KOH, 450 nm LED (440–460 nm, 0.03 W cm −2 ) h 0.01 M KOH, 410 nm LED (400–420 nm, 0.03 W cm −2 ) …”
Section: Introductionmentioning
confidence: 99%
“…54 Au/TiO 2 heterostructure photocatalysts have attracted considerable attention due to the LSPR and high effect of charge carrier separation via the formation of a Schottky barrier at the Au/TiO 2 interface according to the previous reports. 55,56 The Au/SDT hierarchical nanorods have been achieved by loading different amount Au NPs on the surface of SDT via using the HAuCl 4 solution of 5, 20, 40, 60, 80 mL as Au precursor, named as Au/SDT-5, Au/SDT-20, Au/SDT-40, Au/SDT-60, Au/SDT-80, respectively. The different loading amounts of Au have a strong effect on the photocatalytic activity as shown in Fig.…”
Section: E Photocatalytic Activitymentioning
confidence: 99%